Regressing anaplastic CD30-positive large-cell lymphoma of the skin - Skiljević, Dušan (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Originally believed to be of histiocytic origin, regressing primary cutaneous anaplastic large-cell lymphoma is a CD30 (Ki 1) positive T-cell lymphoma with histologic high grade malignancy, but with an often favorable clinical course with regression of individual lesions. We present a case of a 69-year-old white woman with an 8-month history of noduloulcerative lesions on her right lower leg, otherwise in good general health. The clinical, histologic, and immunohistochemical findings pointed to CD30 positive primary cutaneous anaplastic large-cell lymphoma. There were no signs of generalization, lymph node or internal organ involvement. After 2 years of activity, the disease regressed. During the 10-year follow-up period, no signs of disease reactivation were noted. Accurate recognition of this lymphoma is important toavoid unnecessary aggressive treatments.
Keywords: Aged; Diagnosis; kožne bolezni; Kožne novotvorbe; limfom; Limfom velikocelični, Ki-1; Lymphoma, Large-Cell, Ki-1; novotvorbe; Pathology; Skin Neoplasms; Starostniki; tumor